Dissolution of fine particle chalcopyrite concentrate in acidic potassium dichromate solution - Ucar, Gokhan; Boyrazli, Mustafa; Aydogan, Salih (My University, 2007)
This paper presents a study for leaching kinetics of chalcopyrite concentrate in acidic potassium dichromate solution. For this purpose effects of stirring speed in the range of 100-400 rpm, sulphuric acid (H2SO4) concentration in the range of 0.1-0.5 M, potassium dichromate (K2Cr2O7) concentration in the range of 0.02-0.1 M, leaching temperature in the range of 20-90°C, particle size fractions of 212×106, 106×75, 74×45, 45×38 and minus 38 ?m and solid/liquid ratio in the range of 10-200 g/L on copper dissolution were investigated. The rate of chalcopyrite oxidation by potassium dichromate in sulphuric acid was directly proportional to stirring speed, sulphuric acid and potassium dichromate concentrations and leaching temperature. On the other hand, it increased with decreasing particle size and solid/liquid ratio. The kinetic study showed that the dissolution of copper from the concentrate is well represented by a shrinking core model controlled by diffusion through a porous layer, 1-2/3X-(1-X)2/3. The activation energy obtained was 22.44 kJ/mol for the temperature range 20-90 °C.
7th International Scientific Conference on Modern Management of Mine Producing, Geology and Environmental Protection, SGEM 2007 -- 11 June 2007 through 15 June 2007 -- Albena -- 101475
Keywords: Chalcopyrite; Potassium dichromate; Shrinking core model; Sulphuric acid